Activation of Fibrinolysis, But Not Coagulation, During End-Ischemic Ex Situ Normothermic Machine Perfusion of Human Donor Livers. Issue 2 (February 2017) - Karangwa, Shanice A.; Burlage, Laura C.; Adelmeijer, Jelle; Karimian, Negin; Westerkamp, Andrie C.; Matton, Alix P.; van Rijn, Rianne; Wiersema-Buist, Janneke; Sutton, Micheal E.; op den Dries, Sanna; Lisman, Ton; Porte, Robert J.
Abstract : Background: Ex situ normothermic machine perfusion (NMP) can be performed after traditional static cold preservation to assess graft function and viability before transplantation. It is unknown whether this results in activation of coagulation and fibrinolysis, as may occur upon graft reperfusion in vivo. Methods: Twelve donor livers declined for transplantation underwent 6 hours of end-ischemic NMP using a heparinized plasma-based perfusion fluid. Concentration of prothrombin fragment F1 + 2 (marker of coagulation activation), D-dimer, plasmin-antiplasmin complex, tissue plasminogen activator and plasminogen activator inhibitor-1 (markers for fibrinolysis) and alanine aminotransferase (ALT) (marker of ischemia-reperfusion [I/R] injury) were measured in perfusion fluid at regular intervals. Liver biopsies were examined for the presence of fibrin, using light microscopy after Maurits, Scarlet and Blue staining. Results: No significant increase in prothrombin F1 + 2 was noted during NMP. D-dimer and plasmin-antiplasmin complex levels increased soon after start of NMP and D-dimer concentrations correlated significantly with levels of tissue plasminogen activator. In livers displaying good function during NMP, perfusate levels of ALT and D-dimers were low (⩽3500 ng/mL), whereas significantly higher D-dimer levels (>3500 ng/mL) were in found in livers with poor graft function. Activation of fibrinolysis correlated significantly with the degree of I/R injury, as reflected by ALT levels. Conclusions: End-ischemic ex situ NMP results in activation of fibrinolysis, but not of coagulation. Markers of fibrinolysis activation correlate significantly with markers of I/R injury. High concentrations of D-dimer early after start of NMP can be considered a marker of severe I/R injury and a predictor of poor liver graft function. Abstract : The evaluation of liver grafts may be enhanced by the use of normothermic perfusion after cold storage. In this study fibrinolysis is enhanced as a correlate of ischemia/reperfusion injury in discarded human liver grafts.